Can Central Bank Mitigate the Effects of the COVID-19 Pandemic on the Macroeconomy?. Issue 9 (15th July 2022) - Long, Han; Chang, Chun-Ping; Jegajeevan, Sujeetha; Tang, Kai
ABSTRACT: Facing with the enormous economic loss resulting from the unexpected outburst of the COVID-19 pandemic, central banks around the world began to show a great activeness and implement numerous monetary policies to help mitigate the negative shocks and recover the economy. This paper aims at investigating the impact of the COVID-19 pandemic on the macroeconomy and whether central bank activeness have helped mitigate the negative shock of the COVID-19. Using the panel fixed effects model and monthly data of 38 countries from January 2020 to June 2021, this paper finds that the COVID-19 pandemic has increased inflation and unemployment apparently. More importantly, central bank activeness has a positive effect on reducing the growing pressure from the COVID-19 on inflation, while it cannot mitigate the shock of the COVID-19 on unemployment rate. Specially, government others measure, including containment and health, and stringency policies, have little effect in mitigating the negative impact of the pandemic on inflation and unemployment. Our findings suggest that the central bank activeness have heterogeneous effects on different macroeconomic indicators, and cannot mitigate the hurts of the COVID-19 pandemic for all macro indicators during the pandemic.